Integrated medical rehabilitation delivery in China - Yue Xiao (KeAi Communications Co., Ltd., 2017)
Currently, China has a growing need for rehabilitative care; however, rehabilitative care has been underdeveloped for decades. Since the end of 2010, pilot programs in 46 cities (districts) of 14 provinces have been initiated by the Ministry of Health in China to establish formal arrangements for facilitating the delivery of continuous medical rehabilitative care for local communities. After 2 years of pilot work, an evaluation was conducted by researchers. This paper reviews the current status of rehabilitative care in China and discusses the findings of the nationwide pilot program on the integrated rehabilitative service. Some key mechanisms and main issues were identified after analyzing the preliminary outcomes of some of the pilot programs. Keywords: Pilot, Medical rehabilitation